2013
DOI: 10.1177/0269881113490328
|View full text |Cite
|
Sign up to set email alerts
|

Functional topography of serotonergic systems supports the Deakin/Graeff hypothesis of anxiety and affective disorders

Abstract: Over 20 years ago, Deakin and Graeff hypothesized about the role of different serotonergic pathways in controlling the behavioral and physiologic responses to aversive stimuli, and how compromise of these pathways could lead to specific symptoms of anxiety and affective disorders. A growing body of evidence suggests these serotonergic pathways arise from topographically organized subpopulations of serotonergic neurons located in the dorsal and median raphe nuclei. We argue that serotonergic neurons in the dors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(84 citation statements)
references
References 207 publications
(271 reference statements)
2
78
0
4
Order By: Relevance
“…Following removal of these component maps, within the DR networks identified we found that HA was significantly correlated with resting activity in the basal amygdala and ventral hippocampus. This is in accordance with the Deakin and Graeff hypothesis, suggesting that serotonergic neurons in the DR project to the basolateral amygdala and ventral hippocampus in the process of mediating conflict and anxiety (Paul & Lowry, 2013). Indeed, it is well-known that the amygdala plays a critical role in emotional regulation and anxiety, and that amygdala dysregulation predisposes an individual to developing anxiety disorders, which are associated with significantly increased HA (Hariri & Whalen, 2011;Pessoa, 2011;Starcevic, Uhlenhuth, Fallon, & Pathak, 1996).…”
Section: Discussionsupporting
confidence: 88%
“…Following removal of these component maps, within the DR networks identified we found that HA was significantly correlated with resting activity in the basal amygdala and ventral hippocampus. This is in accordance with the Deakin and Graeff hypothesis, suggesting that serotonergic neurons in the DR project to the basolateral amygdala and ventral hippocampus in the process of mediating conflict and anxiety (Paul & Lowry, 2013). Indeed, it is well-known that the amygdala plays a critical role in emotional regulation and anxiety, and that amygdala dysregulation predisposes an individual to developing anxiety disorders, which are associated with significantly increased HA (Hariri & Whalen, 2011;Pessoa, 2011;Starcevic, Uhlenhuth, Fallon, & Pathak, 1996).…”
Section: Discussionsupporting
confidence: 88%
“…For example, locomotion is associated with coordinated cardiovascular and respiratory changes, but the extent to which brain pathways regulating exercise-induced cardiorespiratory responses overlap with those regulating stress-evoked cardiorespiratory responses is not known. Another major general issue concerns the role of noradrenergic neurons in the locus coeruleus and serotonergic neurons in the dorsal raphe, both of which are activated during stress and arousal and have widespread projections to many parts of the brain, including key nuclei involved in cardiovascular and respiratory regulation (7,98,124). Furthermore, the nucleus incertus in the pons and lateral habenula in the midbrain have recently been shown to contain neurons that are strongly activated by stress and which also project very widely throughout the brain (73,130).…”
Section: Perspectives and Significancementioning
confidence: 99%
“…In particular, the Deakin/Graeff theory (Deakin and Graeff, 1991) surmises different pathways controlling behavioral responses to aversive stimuli. Thereby, the dorsal raphe periventricular tract is supposed to inhibit 'fight-or-flight' responses by stimulation of 5-HT 1A R and/ or 5-HT 2A R. Disinhibition of this pathway is believed to result in bouts of sympathetic and behavioral arousal comparable to PD (for review, see Paul and Lowry, 2013). The mesencephalic 5-HT 1 R desensitization observed in the present analysis and the resulting disinhibition, thus, are in line with the hypothesized 5-HT 1A R dysfunction in the dorsal raphe periventricular tract.…”
Section: Role Of 5-ht In Neuropsychiatric Disordersmentioning
confidence: 99%